1972
DOI: 10.1530/acta.0.0710374
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of Mestranol to Ethinyloestradiol in Vitro and in Vivo

Abstract: The present concept is that mestranol must be demethylated to ethi nyl \x=req-\ oestradiol in order to have oestrogenic activity. This activation of mestranol has been studied in vivo by means of radiospirometry and in vitro incubations with rat liver microsomes.During the microsomal incubation of doubly labelled [4-14C] mestranol and [3H-methoxy] mestranol with an NADPH-regenerating system 14C\ x=req-\ labelled ethinyloestradiol was formed as the main metabolite, which was identified by crystallization to con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…After administration of [4-HC]mestranol 2.5% of the dose was found as labelled carbon dioxide in the expired air. About 35 % of mestranol appears to be demethylated to ethynyloestradiol in rats (Kappus et al 1972) compared to 60% in mice.…”
Section: G Metabolism Of Oestrogens In Ratsmentioning
confidence: 99%
“…After administration of [4-HC]mestranol 2.5% of the dose was found as labelled carbon dioxide in the expired air. About 35 % of mestranol appears to be demethylated to ethynyloestradiol in rats (Kappus et al 1972) compared to 60% in mice.…”
Section: G Metabolism Of Oestrogens In Ratsmentioning
confidence: 99%
“…The present report extends these observations and indicates a stimulatory effect of phénobar bital on the liver microsomal metabolism of mestranol to formaldehyde and to unidentified polar metabolites. Additional studies by Kappus et al (1972) indicated a stimulatory effect of phénobarbital on the déméthylation of mestranol to ethynylestradiol.…”
Section: Discussionmentioning
confidence: 97%
“…The uterotrophic response to norethynodrel and norethisterone was also inhibited. In an in vitro study Kappus, Bolt & Remmer (1972) observed a three fold increase in the rate of demethylation of mestranol to EE2 in phenobarbitone pretreated rats.…”
Section: Introductionmentioning
confidence: 96%